1997
DOI: 10.1023/b:mebr.0000007107.56266.18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulated Upper Gastrointestinal Hemorrhage on Ammonia and Related Amino Acids in Blood and Brain of Chronic Portacaval-shunted Rats

Abstract: Gastrointestinal (GI) hemorrhage during compromised liver function is known to precipitate portal-systemic encephalopathy (PSE). Hypothetically, the induced hyperammonemia depletes cerebral glutamate pools. To investigate this hypothesis, rats were studied 14 days after portacaval shunt (PCS) or sham surgery (SHAM). Rats received 3 mL bovine erythrocytes or saline at t = 0, 1, 2, and 3h via a previously placed gastrostomy catheter. At t = 0, 2, 4, 6 and 8h arterial blood and at t = 8h cerebral cortex were samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Pyramidal signs are typically present in severe HE [23]; motor tract dysfunction can be demonstrated by transcranial magnetic stimulation in advanced cirrhosis and has been shown to be reversible after liver transplantation [24]. The administration of blood to PCA rats induces changes in behavior and in motor function [25]. In the current study, we assessed motor function using MEP and showed a decrease of the amplitude and a delay on the conduction of MEP after GIB.…”
Section: Discussionmentioning
confidence: 63%
“…Pyramidal signs are typically present in severe HE [23]; motor tract dysfunction can be demonstrated by transcranial magnetic stimulation in advanced cirrhosis and has been shown to be reversible after liver transplantation [24]. The administration of blood to PCA rats induces changes in behavior and in motor function [25]. In the current study, we assessed motor function using MEP and showed a decrease of the amplitude and a delay on the conduction of MEP after GIB.…”
Section: Discussionmentioning
confidence: 63%
“…6 Simulating the metabolic effects of an UGIB by the oral administration of erythrocytes has been shown to induce hyperammonemia and behavioural disturbance in portacaval shunted rats. 7 In a recently published placebo-controlled study, we showed that simulating an UGIB by the oral administration of a specifically prepared amino acid (aa) solution identical to the aa profile of hemoglobin to patients with well-compensated cirrhosis, resulted in hyperammonemia but was not associated with significant deterioration in neuropsychological tests. However, the neuropsychological function in the group administered the placebo improved significantly suggesting that induced hyperammonemia produced a learning difficulty in the population studied.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, laboratory rats proved to be excellent models to study liver cirrhosis 11 , as well as hepatic encephalopathy [31][32][33] . In those experiments the liver atrophy and regeneration 34 , microvascular structural changes 35 , as well as remote effects were studied.…”
Section: Intraoperative Microcirculatory Investigationsmentioning
confidence: 99%